2022
DOI: 10.3389/fimmu.2022.856457
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Immune Regulatory Role of Non-Coding RNAs (miRNAs and lncRNAs) in Insect-Pathogen Interactions

Abstract: Insects are by far the most abundant and diverse living organisms on earth and are frequently prone to microbial attacks. In other to counteract and overcome microbial invasions, insects have in an evolutionary way conserved and developed immune defense mechanisms such as Toll, immune deficiency (Imd), and JAK/STAT signaling pathways leading to the expression of antimicrobial peptides. These pathways have accessory immune effector mechanisms, such as phagocytosis, encapsulation, melanization, nodulation, RNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 186 publications
(192 reference statements)
1
30
0
Order By: Relevance
“…Flies absent of VINR showed a greater susceptibility to infections with virus and bacteria [ 63 ]. Several studies and reviews have addressed and highlighted immune modulatory of miRNAs and both insect- and pathogen-derived lncRNAs that are involved in pathogen-insect cross-talk [ 64 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flies absent of VINR showed a greater susceptibility to infections with virus and bacteria [ 63 ]. Several studies and reviews have addressed and highlighted immune modulatory of miRNAs and both insect- and pathogen-derived lncRNAs that are involved in pathogen-insect cross-talk [ 64 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The objective of the current research was to identify the lncRNAs that target immune-related genes. Recent studies have shown that besides mRNAs, an abundance of miRNAs and lncRNAs affect immune responses during host–pathogen interactions [ 71 , 72 ]. Our analyses identified multiple differentially expressed cis -acting lncRNAs that target crucial immune genes, such as βGRP , Toll-like receptors 3 / 6 , trypsin , transferrin , serpins, and cytochrome P450 during M. anisopliae infection.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are versatile regulators that regulate gene expression in physiological, pathological, and immunological processes (Satyavathi et al, 2017). Accumulated pieces of evidence have confirmed the importance of lncRNAs in the regulation of insectpathogen interactions (Moure et al, 2022;Valanne et al, 2019;Zhang et al, 2021;Zhang, Dong, et al, 2020;Zhang, Yin, et al, 2020). With the support of the RNA sequencing technique, in B. mori, 11,810 lncRNAs have been identified based on 21 RNA-seq databases covering the fat body, silk gland, gonad, brain and Malphghian tubule tissues so far (Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%